Influential Factors Affecting the Adoption Intention of Electric Vehicles in Indonesia: An Extension of the Theory of Planned Behavior - Daffa Refor Multi Ray; Christian Harito (Engineering, MAthematics and Computer Science Journal (EMACS), 2023)
The primary goal of the thesis was to examine the factors that affect the willingness of people in Indonesia to adopt Electric Vehicles (EVs). Given the pressing need in Indonesia to address energy shortages and reduce greenhouse gas emissions, this research aimed to investigate the elements that influence people's inclination to use EVs. In this study, questionnaires were used as a means of measurement. Respondents were provided with a brief explanation before completing the survey. Using an extended TPB (Theory of Planned Behavior) model, the research analyzed the adoption intentions of 310 respondents from Indonesia, following a minimum sample guideline of 200. The collected data was analyzed using smartPLS4 to extract insights. The empirical analysis of the research focused on five key factors: attitude, subjective norms, perceived behavioral control, environmental concern, and moral norms. Notably, the empirical results showed that while attitude had an insignificant impact on the adoption intention of EVs in Indonesia, the other factors subjective norms, perceived behavioral control, environmental concern, and moral norms had a significant and positive influence on the intention to embrace electric vehicles in the country. Based on these findings, it can be concluded that the extended TPB model is suitable for predicting the adoption intention of electric vehicles. Considering these results, the study explores the implications for EV adoption in Indonesia, offering valuable insights and recommendations for future research and for the Indonesian government's decision-making process regarding the factors that influence EV adoption.